Methods of motivation capacity Group Reluctance Negative Information-Psychological Influence upon Interior Troops enlisted man in composition Department of Territorial Command - Drobakha, H. А.; Lіpatov, І. І.; Hunbіn, K. Yu.; Lіpatova, S. L. (Honor and Law, 2019)
Approaches to motivation of number of the group reluctance negative information-psychological influence Interior Troops enlisted man are defined as a result of analysis contents its work.